2022
DOI: 10.1039/d1fo03622j
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of chlorogenic acid on the meat quality of oxidatively stressed broilers revealed by integrated metabolomics and antioxidant analysis

Abstract: Oxidation is a major cause of meat quality deterioration during broiler production, leads to the undesirable meat color, impaired water holding capacity (WHC) and thereby impacting consumer appeal and satisfaction....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
5
16
0
Order By: Relevance
“…In the present study, CGA increased the GSH content in the intestines of immune-stressed broiler breeders, in agreement with Shi [ 30 ], who found that CGA significantly increased GSH levels in liver tissue and reduced oxidative stress. Several studies have noted that CGA significantly enhanced antioxidant activity in broilers [ 11 , 12 , 25 , 26 ] and pigs [ 13 , 31 ], which was in agreement with our findings. The antioxidant effects of CGA were potentially attributed to its chemical structure for direct scavenging of free radicals and activation of endogenous antioxidant defenses against radicals [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, CGA increased the GSH content in the intestines of immune-stressed broiler breeders, in agreement with Shi [ 30 ], who found that CGA significantly increased GSH levels in liver tissue and reduced oxidative stress. Several studies have noted that CGA significantly enhanced antioxidant activity in broilers [ 11 , 12 , 25 , 26 ] and pigs [ 13 , 31 ], which was in agreement with our findings. The antioxidant effects of CGA were potentially attributed to its chemical structure for direct scavenging of free radicals and activation of endogenous antioxidant defenses against radicals [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…CGA remarkably downregulated serum corticosterone levels, alleviating the stress response of broiler breeders. Our results are in line with other studies showing that dietary CGA supplementation significantly decreased serum corticosterone concentration in DEX-challenged broilers [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After a 30-min blooming period, the meat color parameters, including lightness ( L* ), redness ( a* ) and yellowness ( b* ) values, were measured at room temperature using a colorimeter (CR-410; standard observer, 2°; illuminant, D65; Konica Minota, Inc., Tokyo, Japan), as described by Zhang et al (2022) . The meat color parameters were immediately measured 3 times at different locations of the medial portion of each sample.…”
Section: Methodsmentioning
confidence: 99%
“…Non-targeted liquid chromatography–mass spectrometry has been used to characterize lipid-related metabolites in the muscle of pigs [ 12 ]. Xiao et al adopted 1 H nuclear magnetic resonance spectroscopy to analyze the metabolic composition of chicken meat [ 13 ]. Ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) has been used to investigate the underlying mechanisms responsible for chlorogenic acid-induced improvements in meat quality of broiler breast muscles [ 14 ].…”
Section: Introductionmentioning
confidence: 99%